2024
DOI: 10.1093/plphys/kiae024
|View full text |Cite
|
Sign up to set email alerts
|

Mind the gap: Epigenetic regulation of chromatin accessibility in plants

Joan Candela-Ferre,
Borja Diego-Martin,
Jaime Pérez-Alemany
et al.

Abstract: Chromatin plays a crucial role in genome compaction and is fundamental for regulating multiple nuclear processes. Nucleosomes, the basic building blocks of chromatin, are central in regulating these processes, determining chromatin accessibility by limiting access to DNA for various proteins, and acting as important signaling hubs. The association of nucleosomes to DNA and the folding of chromatin into higher-order structures are strongly influenced by a variety of epigenetic marks, including DNA methylation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 192 publications
0
4
0
Order By: Relevance
“…Histone methylation and acetylation can influence genome accessibility, at levels ranging from local nucleosome dynamics to the folding of higher chromatin structure. Both methylation and acetylation promote open chromatin conformation and positively influence the genome accessibility [95]. Chromatin immunoprecipitation sequencing (ChIPseq) was used to profile three histone marks, the methylation of histone H3 at lysine 4 (H3K4me3), the methylation of histone H3 at lysine 36 (H3K36me3) and the acetylation of histone H3 at lysine 9 (H3K9ac), among healthy, diseased and MMS-treated diseased P. fortunei plantlets grown in vitro [74,75].…”
Section: Histone Methylation and Acetylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Histone methylation and acetylation can influence genome accessibility, at levels ranging from local nucleosome dynamics to the folding of higher chromatin structure. Both methylation and acetylation promote open chromatin conformation and positively influence the genome accessibility [95]. Chromatin immunoprecipitation sequencing (ChIPseq) was used to profile three histone marks, the methylation of histone H3 at lysine 4 (H3K4me3), the methylation of histone H3 at lysine 36 (H3K36me3) and the acetylation of histone H3 at lysine 9 (H3K9ac), among healthy, diseased and MMS-treated diseased P. fortunei plantlets grown in vitro [74,75].…”
Section: Histone Methylation and Acetylationmentioning
confidence: 99%
“…DNA methylation participates in various nuclear processes such as gene expression, DNA repair and recombination. Various studies have indicated that DNA methylation at gene boundaries contributes to a differential gene expression in response to pathogens [95]. Methylation-sensitive amplification polymorphism (MSAP) analysis revealed that the DNA methylation level of healthy plantlets is higher than the PaWB-diseased ones.…”
Section: Dna Methylationmentioning
confidence: 99%
“…The existing epigenetic patterns with distinct distribution and level of methylation, acetylation and other epigenetic marks can form epialleles, which are stably carried on to the future generations. 46 …”
Section: Memory Formationmentioning
confidence: 99%
“…Both proteins have an ATPase domain which is inserted by the prominent Domain II (DII) with a characteristic oligonucleotide/oligosaccharide binding-fold (OB-fold) responsible for protein-protein interactions. Rvb1/RuvBL1 and Rvb2/RuvBL2 are shared with other complexes involved in chromatin remodeling, such as SWR1 and INO80-C (Candela-Ferré et al, 2024). Yeast Tah1 is a small protein (12 KDa) consisting almost exclusively of a carboxylate clamp-type TPR domain that interacts with the C-terminal peptide MEEVD of HSP90 and is thus responsible for the recruitment of the chaperone to the R2TP complex (Zhao et al, 2005).…”
Section: Introductionmentioning
confidence: 99%